Chromatin Changes at the PPAR‐γ2 Promoter During Bone Marrow‐Derived Multipotent Stromal Cell Culture Correlate With Loss of Gene Activation Potential. (26th May 2015) - Lynch, Patrick J.; Thompson, Elaine E.; McGinnis, Kathleen; Rovira Gonzalez, Yazmin I.; Lo Surdo, Jessica; Bauer, Steven R.; Hursh, Deborah A.
Abstract Bone marrow‐derived multipotent stromal cells (BM‐MSCs) display a broad range of therapeutically valuable properties, including the capacity to form skeletal tissues and dampen immune system responses. However, to use BM‐MSCs in a clinical setting, amplification is required, which may introduce epigenetic changes that affect biological properties. Here we used chromatin immunoprecipitation to compare post‐translationally modified histones at a subset of gene promoters associated with developmental and environmental plasticity in BM‐MSCs from multiple donors following culture expansion. At many locations, we observed localization of both transcriptionally permissive (H3K4me3) and repressive (H3K27me3) histone modifications. These chromatin signatures were consistent among BM‐MSCs from multiple donors. Since promoter activity depends on the relative levels of H3K4me3 and H3K27me3, we examined the ratio of H3K4me3 to H3K27me3 (K4/K27) at promoters during culture expansion. The H3K4me3 to H3K27me3 ratios were maintained at most assayed promoters over time. The exception was the adipose‐tissue specific promoter for the PPAR‐γ2 isoform of PPAR‐γ, which is a critical positive regulator of adipogenesis. At PPAR‐γ2, we observed a change in K4/K27 levels favoring the repressed chromatin state during culture. This change correlated with diminished promoter activity in late passage cells exposed to adipogenic stimuli. In contrast to BM‐MSCs and osteoblasts, lineage‐restricted preadipocytes exhibited levels of H3K4me3 and H3K27me3 that favored the permissive chromatin state at PPAR‐γ2. These results demonstrate that locus‐specific changes in H3K4me3 and H3K27me3 levels can occur during BM‐MSC culture that may affect their properties. Stem Cells 2015;33:2169–2181